The influence of micronutrients on the recovery of soccer players: Narrative review (Research, Society and Development, 2026)
The physical demands of soccer involve high-intensity intermittent efforts, distances of 11-13 km per match, and the generation of reactive oxygen species (ROS). This scenario triggers oxidative stress, exercise-induced muscle damage (EIMD), inflammation, and delayed-onset muscle soreness (DOMS), compromising recovery within the short 48-72h intervals of the congested Brazilian calendar. This study aimed to synthesize scientific evidence regarding the impact of micronutrients on soccer players' recovery. A narrative review was conducted using PubMed and BVS databases, selecting primary studies published between 2020 and 2025 focusing on vitamins C, D, E, zinc, omega-3, and polyphenols in high-intensity athletes. Findings indicate that supplements such as vitamin C (1000 mg/day), vitamin D (6000 IU/day), curcumin (300-1400 mg/day), astaxanthin, beetroot, and chokeberry reduce markers of inflammation (IL-6, CRP), muscle damage (CK, LDH), and oxidative stress (MDA, 8-OHdG). Performance effects (VO2max and agility) were inconsistent, depending on initial redox status, dose, and duration. Excessive doses may inhibit physiological adaptations like mitochondrial biogenesis and hypertrophy. Results suggest that micronutrients optimize recovery when applied in a balanced and individualized manner. Specific guidelines are required in Brazil, where local protocols are lacking, justifying further research with larger samples and synergistic combinations to reduce reliance on anti-inflammatories and overtraining risks.